2006
DOI: 10.1002/anie.200503271
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Induced Acoustic Desorption Mass Spectrometry of Single Bioparticles

Abstract: Single charged bioparticles such as viruses, bacteria, and mammalian whole cells have been successfully desorbed by laser‐induced acoustic waves and analyzed with a quadrupole ion‐trap mass spectrometer (see picture). This approach offers a high sensitivity of detection and good accuracy of the mass measurement. The capability to measure the mass of an entire cell has broad potential in biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 24 publications
3
51
0
Order By: Relevance
“…"Large and heavy" objects weakly bound to the substrate surface may be then kinematically removed from it ("shaken-off"). This could indeed serve as an explanation of observations from recent experiments where the desorption of intact viruses and biological cells were reported (Peng, Yang et al 2006). However, this regime cannot be connected with generation of the acoustic waves but most likely corresponds to a physically different mode of shock-wave generation (Menikoff 2007).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…"Large and heavy" objects weakly bound to the substrate surface may be then kinematically removed from it ("shaken-off"). This could indeed serve as an explanation of observations from recent experiments where the desorption of intact viruses and biological cells were reported (Peng, Yang et al 2006). However, this regime cannot be connected with generation of the acoustic waves but most likely corresponds to a physically different mode of shock-wave generation (Menikoff 2007).…”
supporting
confidence: 67%
“…Various approaches for the ionization of the desorbed molecules were successfully employed, among them: electron impact and chemical ionization , single-photon ionization (SPI) (Zinovev, Veryovkin et al 2007), as well as Elecro-Spray Ionization (ESI) (Cheng, Huang et al 2009). Moreover, the ability of the LIAD process to non-destructively eject from solid surfaces not only single molecules but also larger intact biological particles, such as viruses (Peng, Yang et al 2006) and 1 µm size tungsten particles (Menezes, Takayama et al 2005) have been demonstrated. In our opinion, the wider spread of LIAD among analytical MS applications is now limited by the lack of an adequate theoretical concept able to explain the existing observations and to predict optimal experimental conditions for future measurements.…”
Section: Laser-induced Acoustic Desorptionmentioning
confidence: 99%
“…Recently, single cell trapping and measurement of the mass of a single cell [123][124][125] have been demonstrated. It should be straightforward to blast the cell with a high power pulsed laser beam to release the chemical components such as DNA, protein, lipid, etc.…”
Section: Sensitivity Improvementmentioning
confidence: 99%
“…Xu has shown that it is possible to remove N h (t) by a harmonic interference cancellation algorithm, which cancels the N h (t) completely, reduces N w (t) and retains the signal without distortion [11]. In this study, we apply the algorithm to remove the time-domain electronic noises in the ion signals acquired with a home-built laser desorption/ ionization charge detection ion trap mass spectrometer (LDCD-ITMS) [22][23][24][25][26][27].…”
mentioning
confidence: 99%
“…We know of no methods reported to remove the N RF (t) due to coupling of S x (t) with the rf driving voltage. Here, we present an OWPD method to achieve the task and show that N RF (t) is the dominant noise in the mass spectra obtained with LDCD-ITMS [22][23][24][25][26][27][28][29]. The removal of N RF (t) is critically important in our application of the LDCD-ITMS technique to measure the masses of nanometer-sized particles, of which higher rf frequencies are required for the trapping.…”
mentioning
confidence: 99%